Trabalho, tempo livre e lazer: as possibilidades de liberdade no capitalismo contemporâneo - Custodio, Mariana Lopes (2012)
The investigative problem that gives rise to this dissertation is related to the antinomy leisure and work, considering in this relation the theme of freedom. The objective of this paper is to reflect on the centrality of work as a privileged category for understanding the social being and the possibilities of freedom. We undertook, therefore, a literature search to show how the ways of organizing work processes -Fordism-Taylorism and the Toyota model - bring new values and changes in the way of managing free time and leisure. From this observation, we point out, firstly, how leisure is configured in the discourse of the authors perspective as a time of enjoyment and freedom or on the other hand give the status of leisure entertainment. Such analysis allows us to affirm, that the notions of pleasure / freedom and pleasure / leisure, fit forms of organizing work processes submitted to the logic of capital appreciation. Thus, at first it confirms the split work time and free time and incurs a second time in an attempt to suppress the contradictions of social time